2024
DOI: 10.1126/science.adk6160
|View full text |Cite
|
Sign up to set email alerts
|

Transition of human γ-tubulin ring complex into a closed conformation during microtubule nucleation

Cláudia Brito,
Marina Serna,
Pablo Guerra
et al.

Abstract: Microtubules are essential for intracellular organization and chromosome segregation. They are nucleated by the γ-tubulin ring complex (γTuRC). However, isolated vertebrate γTuRC adopts an open conformation that deviates from the microtubule structure, raising the question of the nucleation mechanism. Here we determine cryo-electron microscopy structures of human γTuRC bound to a nascent microtubule. Structural changes of the complex into a closed conformation ensure that γTuRC templates the 13-protofilament m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Thus, microtubule nucleation is promoted by microtubule-associated proteins (MAPs) or protein complexes that locally concentrate tubulin dimers ( Tovey and Conduit, 2018 ). The best-characterized nucleator is the multi-protein γ-tubulin ring complex (γ-TuRC), which templates the lateral assembly of tubulin dimers to form a 13-protofilament microtubule that extends with its plus-end growing away from the γ-TuRC ( Kollman et al, 2011 ; Brito et al, 2024 ). γ-TuRC activity is normally low in the cytosol but increases on recruitment to specific sites called microtubule-organizing centers (MTOCs) ( Sanchez and Feldman, 2016 ; Tillery et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, microtubule nucleation is promoted by microtubule-associated proteins (MAPs) or protein complexes that locally concentrate tubulin dimers ( Tovey and Conduit, 2018 ). The best-characterized nucleator is the multi-protein γ-tubulin ring complex (γ-TuRC), which templates the lateral assembly of tubulin dimers to form a 13-protofilament microtubule that extends with its plus-end growing away from the γ-TuRC ( Kollman et al, 2011 ; Brito et al, 2024 ). γ-TuRC activity is normally low in the cytosol but increases on recruitment to specific sites called microtubule-organizing centers (MTOCs) ( Sanchez and Feldman, 2016 ; Tillery et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, γ-TuRC’s overall architecture is splayed open compared to the microtubule such that the template is imperfect with low activity in vitro 10 , 12 , 13 . Nevertheless, computational modeling, nucleation assays using purified components, and structural studies have demonstrated that assembly of tubulin onto the γ-TuRC template provides sufficient lateral bond energy to close the γ-TuRC ring, a conformation in which spoke 14 overlaps and occludes spoke 1 10 , 12 , 14 , 15 . γ-TuRC thus consistently nucleates and caps 13 protofilament microtubules 14 – 16 .…”
Section: Introductionmentioning
confidence: 99%